Reviewing the Van Hiele model and the application of metacognition on geometric thinking - Muhammad Ammar Naufal; Abdul Halim Abdullah; Sharifah Osman; Mohd Salleh Abu; Hisyam Ihsan; Rondiyah Rondiyah (Institute of Advanced Engineering and Science, 2021)
Metacognition, or the ability to think about thinking, is essential in the development of geometric thinking. However, studies on the Van Hiele model and the application of metacognition on geometric thinking are still under-researched. This study aimed to provide a review of the Van Hiele model and the application of metacognition on geometric thinking. A total of 844 articles were retrieved through internet search engines from 1995 to 2020 and manually selected and reviewed systematically. The keywords used related to the Van Hiele model, metacognition, and geometric thinking. The findings that emerged from the review were categorized into two main themes which were the effectiveness of the Van Hiele model towards geometric thinking and the effectiveness of the application of metacognition on geometric thinking. Most articles revealed the positive indication of the geometric thinking development through the Van Hiele model intervention. It also seems that the potential of the application of metacognition in the Van Hiele model can strengthen geometric thinking development. Researchers and educators may find this knowledge useful in conducting empirical studies and developing learning instructions based on the application of metacognition in the development of geometric thinking.